2020
DOI: 10.4103/picr.picr_206_19
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and retention of the participants in clinical trials: Challenges and solutions

Abstract: Drug development is a tedious and expensive procedure and it takes roughly 10 to 15 years to take a potential treatment from bench to bedside and costs the pharmaceutical companies as much as USD ~2 billion for the process. Delay in investigator-initiated studies can cause financial loss to grant providers (either public or private) and investigator's reputation may also be at stake. Participant recruitment and retention are two major bottlenecks in conducting clinical trials and contribute vastly to the delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Reducing the intensity of monitoring also reduces the inconvenience of traveling, which in turn helps address existing issues with patient retention in clinical trials. Patient drop-out and insufficient recruitment are often the cause of trials failing to complete accrual within the study period [ 61 ]. This is frustrating from a clinical perspective, as it prolongs the approval of beneficial therapies to reach a wider patient population.…”
Section: Lessons Learnt For the Future Of Oncology Clinical Trialsmentioning
confidence: 99%
“…Reducing the intensity of monitoring also reduces the inconvenience of traveling, which in turn helps address existing issues with patient retention in clinical trials. Patient drop-out and insufficient recruitment are often the cause of trials failing to complete accrual within the study period [ 61 ]. This is frustrating from a clinical perspective, as it prolongs the approval of beneficial therapies to reach a wider patient population.…”
Section: Lessons Learnt For the Future Of Oncology Clinical Trialsmentioning
confidence: 99%
“…This in turn easy the recruitment process by making sure potential participants are timely located and enrolled into HIV clinical trials. It has been reported that delays (from bench to bedside use of the investigational product) encountered in most clinical trials are attributed to faults in the recruitment process, and the way out of this, is to equally involve all stakeholders prior to recruitment [ 32 ]. For that reason, CAB members should not be left out in the recruitment process, instead, are to be treated as equal partners (their opinion matters) when preparing a recruitment plan.…”
Section: Discussionmentioning
confidence: 99%
“…It can analyze a large amount of clinical records of patients to determine their eligibility for a given study. Recruitment of volunteers is one of the many bottlenecks in conducting clinical trials [ 122 ]. It is often the most time-consuming and expensive step.…”
Section: Role Of Ai In Peptide Vaccine Developmentmentioning
confidence: 99%